A novel pre-treatment for the methane production from microalgae by using N-methylmorpholine-N-oxide (NMMO). (February 2016) - Caporgno, M.P.; Olkiewicz, M.; Pruvost, J.; Lepine, O.; Legrand, J.; Font, J.; Bengoa, C.
Abstract : Graphical abstract: Highlights: The NMMO damages the N. oculata cells, increasing the biodegradability. The lipid fraction remains inside the microalgae cells after the pre-treatment. The drying of C. vulgaris may have reduced the effectiveness of the pre-treatment. The NMMO could be fully recycled since does not decompose during the pre-treatment. Abstract: The aim of this work was to study the effect of the solvent N-methylmorpholine-N-oxide (NMMO) to pre-treat Nannochloropsis oculata before the anaerobic digestion process. The results indicated that the pre-treatment affects the characteristics of the cell wall, which consequently becomes more susceptible to the microorganisms attack during anaerobic digestion. The methane production was increased by 43% after the pre-treatment, from 238 ± 6 mLCH4 /gVS until 339 ± 4 mLCH4 /gVS . On the contrary, the methane production from Chlorella vulgaris decreased after the pre-treatment from 251 ± 4 mLCH4 /gVS to 231 ± 3 mLCH4 /gVS . The failure on the pre-treatment was attributed to the particular characteristics of the substrate in consequence of a previous drying step.